CONSTITUTIONAL REGULATION OF THE IMPLEMENTATION OF INTERNATIONAL TREATIES IN SOVEREIGN KAZAKHSTAN - Abaideldinov , Ербол Мусинович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The article discusses the formation of approaches to constitutional regulation in the implementation of international law on the territory of Kazakhstan since the adoption of the first Constitution to the present. It is noted that the country seeks to implement all international treaties concluded on a bilateral and multilateral basis, in accordance with generally accepted principles and norms of international law. At the same time, there is a certain evolution in the country of approaches to the normative regulation of the implementation of international treaties since the adoption of the first Constitution in 1993 to the Basic Law of 1995. In addition, the reader’s attention was drawn to the amendments and additions made to the Constitution of the Republic of Kazakhstan, adopted on March 10, 2017, which provide for a number of measures to improve the balance between international and domestic law, which makes it possible to be more careful, without any insurmountable contradictions the law of the country, on the basis of all applicable domestic legislation, to approach the fulfillment of international obligations assumed by the country. The authorities of the Constitutional Council of the Republic of Kazakhstan to consider international treaties prior to ratification for compliance with their Constitution, as well as the additional powers of this body of constitutional control, introduced on March 10, 2017 among amendments and additions to the Constitution, are considered. It was concluded that in Kazakhstan, at the constitutional and legislative levels, all necessary measures are taken to fulfill international obligations in good faith, to prevent any conflicts of international obligations and national peculiarities of the country, to preserve and strengthen the sovereignty of the state.